A preliminary research and notes on Orthoptera (Insecta) Fauna of Hakkari Province - Taylan Mehmet Sai̇t; Şi̇ri̇n Deni̇z; Sevgi̇li̇ Hasan; Yeşi̇lyurt Fati̇h (Zootaxa, 2021)
To date several studies have been carried out on Orthoptera fauna throughout Anatolia; however, there is no comprehensive study on the Orthoptera fauna of Hakkari Province. This study is a preliminary comprehensive research that deals with the less known Orthoptera (Insecta) fauna of Hakkari Province. In this respect, the records and possible localities were examined between the years 2018–2020 (except Kurdia uvarovi) for the Hakkari Province. Specimens were collected with the help of an insect sweep net or by hand. As a result of the field studies and literature research, it has been determined that the Orthoptera fauna in the province is represented by 51 genera and 69 species/subspecies belonging to 19 subfamilies in 8 families. In the study, 24 new records were noted for Hakkari Orthoptera fauna and Isophya iraca Maran, 1977 (syn. n), which is established as a new synonym of I. hakkarica Karabag, 1962. According to our preliminary research, the Orthoptera fauna of Hakkari includes 32 Ensiferan and 37 Caeliferan members. In the Ensifera suborder (long antennae katydids, crickets and allies), 25 species belonging to the Tettigoniidae, 5 species belonging to Gryllidae, and one species for the each of Myrmecophilidae and Gryllotalpidae families have been identified. Caelifera suborder includes 26 species belonging to the Acrididae, 9 species belonging to the Pamphagidae, and one species for each of the Pyrgomorphidae and Tetrigidae families. During the field studies, it was observed that the Uvarovistia satunini (Uvarov, 1916), Uvarovistia zebra (Uvarov, 1916) and, Bradyporus (Callimenus) latipes (Stål, 1875) species have high population densities. They “swarm” and damage the agricultural areas especially in the Durankaya, Bayköy, Bağışlı, and Kırıkdağ regions. For this reason, it is suggested that the populations of these species should be routinely monitored in agricultural areas.